2023
DOI: 10.1101/2023.03.14.532615
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insufficient evidence for natural selection associated with the Black Death

Abstract: Klunk et al. analyzed ancient DNA data from individuals in London and Denmark before, during and after the Black Death [1], and argued that allele frequency changes at immune genes were too large to be produced by random genetic drift and thus must reflect natural selection. They also identified four specific variants that they claimed show evidence of selection including at ERAP2, for which they estimate a selection coefficient of 0.39-several times larger than any selection coefficient on a common human vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Klunk et al (2022) look at ancient DNA samples from Britian and suggest instead a dramatically different model of extreme and periodic soft selective sweeps 58 . This hypothesis does align with Evershed et al (2022) who used milk residues in archaeological pottery to argue against the hypothesis of coevolution with dairying practices 59 , but the Klunk et al data analysis has been criticized for technical and conceptual errors 60 .…”
Section: Resultssupporting
confidence: 61%
“…Klunk et al (2022) look at ancient DNA samples from Britian and suggest instead a dramatically different model of extreme and periodic soft selective sweeps 58 . This hypothesis does align with Evershed et al (2022) who used milk residues in archaeological pottery to argue against the hypothesis of coevolution with dairying practices 59 , but the Klunk et al data analysis has been criticized for technical and conceptual errors 60 .…”
Section: Resultssupporting
confidence: 61%
“…The high correlation in allele frequency of common variants [minor allele frequency (MAF) > 0.1 in Klunk et al ( 16 ) data] between our Cambridge cohort and the London/Danish cohort and the fact that we got qualitatively similar results when using the same variant lists suggest that differences in genotyping, either with or without imputation, are not likely the key factors; our results show that the subset of 250 regions used by Klunk et al ( 16 ) are likely to contain too few variants to be robustly representative of variation in the full list of 37,574 neutral regions defined by Gronau et al ( 38 ). Furthermore, Barton et al ( 50 ) have shown that the enrichment of high F ST variants at immune loci in Klunk et al ( 16 ) results is attributable to a statistical artifact caused by different coverage of loci. Although not supporting the results of Klunk et al ( 16 ) study, our results are in line with other research showing relatively low or moderate differentiation of immunity genes by F ST ( 51 , 52 ).…”
Section: Discussionmentioning
confidence: 98%
“…This study reported an overall enrichment of allele frequency differentiation in immune genes as well as a handful of potential targets under positive selection. However, serious skepticism has been raised towards the findings due to technical concerns [ 42 ], and other studies adopting similar designs (though with smaller sample sizes) failed to replicate the selection signals at immune genes overall or at individual candidates [ 43 , 44 ]. These results suggest the selection effects of historical pandemics at individual genomic loci are relatively modest, necessitating expansive sample sizes for detection.…”
Section: Positive Selection At Individual Genomic Locimentioning
confidence: 99%